Obesity, Adipose Tissue and Vascular Dysfunction. Issue 7 (2nd April 2021) - Koenen, Mascha; Hill, Michael A.; Cohen, Paul; Sowers, James R.
Abstract : Cardiovascular diseases are the leading cause of death worldwide. Overweight and obesity are strongly associated with comorbidities such as hypertension and insulin resistance, which collectively contribute to the development of cardiovascular diseases and resultant morbidity and mortality. Forty-two percent of adults in the United States are obese, and a total of 1.9 billion adults worldwide are overweight or obese. These alarming numbers, which continue to climb, represent a major health and economic burden. Adipose tissue is a highly dynamic organ that can be classified based on the cellular composition of different depots and their distinct anatomical localization. Massive expansion and remodeling of adipose tissue during obesity differentially affects specific adipose tissue depots and significantly contributes to vascular dysfunction and cardiovascular diseases. Visceral adipose tissue accumulation results in increased immune cell infiltration and secretion of vasoconstrictor mediators, whereas expansion of subcutaneous adipose tissue is less harmful. Therefore, fat distribution more than overall body weight is a key determinant of the risk for cardiovascular diseases. Thermogenic brown and beige adipose tissue, in contrast to white adipose tissue, is associated with beneficial effects on the vasculature. The relationship between the type of adipose tissue and its influence on vascular function becomes particularly evident in the context of the heterogenous phenotype of perivascular adipose tissue that is strongly location dependent. In this review, we address the abnormal remodeling of specific adipose tissue depots during obesity and how this critically contributes to the development of hypertension, endothelial dysfunction, and vascular stiffness. We also discuss the local and systemic roles of adipose tissue derived secreted factors and increased systemic inflammation during obesity and highlight their detrimental impact on cardiovascular health.